Multicenter historical cohort study of the relationship between shift work and blood pressure - Mohammad Gholami-Fesharaki; Anoshirvan Kazemnejad; Farid Zayeri; Mohsen Rowzati; Javad Sanati; Hamed Akbari (ARYA Atherosclerosis, 2014)
BACKGROUND: Regarding the relationship between blood pressure (BP) and shift work (SW), previous studies have reported contradictory results. In the present study, we used Bayesian multilevel modeling to evaluate the association of SW and BP after controlling some confounding factors. METHODS: Data of this multicenter historical study were extracted from annual observations of the male workers of Isfahan’s Mobarakeh Steel Company (IMSC) and Polyacryl Iran Corporation (PIC) in Isfahan, Iran, between 2003 and 2011. In this research, we assessed the effect of SW on systolic BP (SBP) and diastolic BP (DPB) with controlling body mass index, age, work experience, marriage, and education status. RESULTS: A total of 8613 (IMSC, n = 5314 and PIC, n = 3299) workers participated in this study with a mean [standard deviation (SD)] age of 41.60 (8.30) and mean (SD) work experience of 16.17 (7.89) years. In this study, after controlling confounding factors, we found no significant relationship between SW and SBP and DBP. CONCLUSION: In general, the results of this multicenter cohort study did not support a relationship between SW and BP. We suggest prospective studies with controlling more confounding factors in this area.